Fertility of predominantly Bos taurus beef cows exposed to fixed-time artificial insemination protocols with intravaginal inserts containing different amounts of progesterone - Pessoa, Gilson Antônio (2025)
The aims of this study were to: 1) evaluate the impact of intravaginal progesterone (P4) inserts containing different amounts of P4 on pregnancy rates of predominantly Bos taurus beef cows exposed to fixed-time artificial insemination (FTAI) using estradiol and P4-based synchronization protocols, and 2) evaluate the impact of delayed luteolysis on the fertility of cows receiving P4 insert with less P4. Cows (n = 1744) were randomly assigned to 1 of 3 treatments: 1) 2.0 mg of estradiol benzoate together with an intravaginal P4-releasing insert containing 1.9 g of P4 (CIDR) on Day 0; 12.5 mg of dinoprost tromethamine on Day 7; 300-IU of equine chorionic gonadotropin together with 0.6 mg of estradiol cypionate and CIDR withdrawal on Day 9 (CIDR-PG7); 2) cows were exposed to the same treatment as CIDR-PG7, however a different intravaginal insert containing 0.5 g of P4 (DIB 0.5) was utilized (DIB-PG7); and 3) cows were exposed to the same synchronization treatment as DIB-PG7, however a dinoprost tromethamine injection was administered on Day 9 instead of Day 7 (DIB-PG9). All cows received a fixed-time artificial insemination (FTAI) 48 h after P4 inserts CIDR removal (Day 11). Circulating concentrations of P4 on Day 9 were greater (P < 0.01) in cows receiving CIDR-PG7 than in cows receiving DIB-PG7 or DIB-PG9. Dominant follicle diameter on Day 9 was greater (P < 0.01) in DIB-PG7 compared with CIDR-PG7 or DIB-PG9, but not different (P > 0.10) between CIDR-PG7 and DIB-PG9 treatments. Follicle diameter on Day 11 did not differ between CIDR-PG7 and DIB-PG7 (P > 0.10), which were greater compared with DIB-PG9 (P < 0.01). Dominant follicle growth between Days 9 and 11 was greater (P < 0.01) in cows receiving CIDR-PG7 than in cows receiving DIB-PG7 and DIB-PG9, which were not different (P = 0.18) among them. Pregnancy rates on experimental Days 41 and 131 were greater (P < 0.01) in cows receiving CIDR-PG7 (59.4 %; 55.5 %) compared with DIB-PG7 (40.1 %; 34.4 %) or DIB-PG9 (45.2 %; 41.4 %) cows. Compared with cows receiving DIB-PG7, cows receiving DIB-PG9 treatment tended (P = 0.08) to have a greater pregnancy rate on experimental Day 41 and 131 (P = 0.06). In summary, intravaginal P4 inserts with only 0.5 g of P4 resulted in decreased circulating concentrations of P4 and decreased pregnancy rates. Delaying induction of luteolysis only partially mitigated this negative outcome.